SOCIOCULTURAL DETERMINANTS OF CARE HOME UTILIZATION AMONG THE ELDERLY IN AKWA IBOM STATE, NIGERIA - Edet, Nse-Abasi Edighienyong; Assi, Victor Eyo (African Journal of Social and Behavioural Sciences, 2025)
The services of care homes are not widely utilised by the elderly in Nigeria and other countries, particularly in culturally communal societies such as Akwa Ibom State, where demographic changes are observed. The study explores the sociocultural factors influencing elder care decisions across four purposively selected Local Government Areas (LGAs) of Akwa Ibom State, by employing a convergent parallel mixed-methods design. Quantitative data were collected from 381 adult respondents using a structured questionnaire, while qualitative insights were derived from twelve (12) key informant interviews involving religious leaders, health workers, and community elders. Beliefs on filial obligation, spiritual continuity, and moral duty contribute to resistance to institutional care. Religious beliefs and community demands support these norms. The increasing readiness of care homes is influenced by such factors as urbanisation and education level. Challenges identified include affordability, regulatory gaps, and limited community awareness. The findings indicate that there has been a cultural shift of traditional caregiving towards formal eldercare. Therefore, an integrated system, which is composed of cultural beliefs, religious lobbying, and policy changes, is suggested. Lastly, the study has contributed to gerontology in sub-Saharan Africa by providing a culturally specific model of eldercare behaviour and resistance.